Kontribusi Repong Damar terhadap Ekonomi Regional dan Distribusi Pendapatan - Wijayanto, Nurheni (Institut Pertanian Bogor (IPB University), 2002)
This research has aims to learn the contribution of Repong Damar to regional economic and income distribution. The data for research consists of primary and secondary data. The secondary data is collected for the analysis of regional economic, and the primary data is used to calculate the income distribution. The analysis of regional economic with Location Quotient (LQ), and Gini Index is used to analysis the income distribution. The result showed that damar sector had become base activities and had positive economic growth at West Lampung. The value of Gini Index is 0.356 for South Pesisir District, 0.300 for Central Pesisir District, and 0.526 for North Pesisir District. The value of Gini Index for Pesisir Krui Region is 0.394. This value shows that Repong Damar had main contributed on income distribution in Pesisir Krui Region.